Upscale of recombinant α-L-rhamnosidase production by Pichia pastoris MutS strain - Markošová, Kristína; Weignerova, Lenka; Rosenberg, Michal; Křen, Vladimír; Rebroš, Martin (Frontiers in Microbiology, 2015)
Pichia pastoris is currently one of the most preferred microorganisms for recombinant enzyme production due to its efficient expression system. The advantages include the production of high amounts of recombinant proteins containing the appropriate posttranslational modifications and easy cultivation conditions. α-L-Rhamnosidase is a biotechnologically important enzyme in food and pharmaceutical industry, used for example in debittering of citrus fruit juices, rhamnose pruning from naringin or enhancement of wine aromas, creating a demand for the production of an active and stable enzyme. The production of recombinant α-L-rhamnosidase cloned in the MutS strain of Pichia pastoris KM71H was optimized. The encoding gene is located under the control of the AOX promoter, which is induced by methanol whose concentration is instrumental for these strain types. Fermentation was upscaled in bioreactors employing various media and several methanol-feeding strategies. It was found that fed batch with BSM media was more effective compared to BMMH media due to lower cost and improved biomass formation. In BSM medium, the dry cell weight reached approximately 60 g/L, while in BMMH it was only 8.3 g/L, without additional glycerol, which positively influenced the amount of enzyme produced. New methanol feeding strategy, based on the level of dissolved oxygen was developed in this study. This protocol that is entirely independent on methanol monitoring was up scaled to a 19.5-L fermenter with 10-L working volume with the productivity of 13.34 mgprot/L/h and specific activity of α-L-rhamnosidase of 82 U/mg. The simplified fermentation protocol was developed for easy and effective fermentation of Pichia pastoris MutS based on dissolved oxygen monitoring in the induction phase of an enzyme production.